Dampak Ukuran Perusahaan, Kualitas Kantor Akuntan Publik (KAP), dan Rasio Keuangan terhadap Audit Delay - Permatasari, Maulina Dyah; Widiastuti, Widiastuti (Universitas Bina Sarana Informatika, 2023)
The COVID-19 pandemic has had an impact on various sectors of business operations, one of which pertains to the occurrence of audit delays. Companies experienced more instances of audit delays in their financial statements in 2019 compared to the subsequent year. This forms the basis for researching the factors influencing these instances of audit delay. The primary objective of this study was to analyze how company size, KAP quality solvency, and profitability affect audit delays. The study's sample consisted of companies within the consumer goods industry sector listed on the Indonesia Stock Exchange from 2019 to 2021. The sampling technique employed was purposive sampling. The analytical method utilized in this research was multiple linear analysis. The findings of the study reveal that audit delays are collectively influenced by company size, KAP quality, solvency, and profitability. While firm size and solvency exhibit no significant individual impact on audit delays, the variables of KAP quality and profitability demonstrate a noteworthy negative effect. The explanatory power of the variables related to company size, KAP quality, solvency, and profitability in clarifying the audit delay variable amounts to 18.7%.